Research Progress on the Application of Multicultural Nursing in End-of-Life Care: A Review - Yange Wang; Dan Liu; Chenjing Shi (Journal of Advances in Social Sciences, 2026)
With the progress of globalisation, providing end-of-life care for all kinds of cultures has become an urgent problem for healthcare systems around the world. Patients and their families from different cultural backgrounds have various views on death, decisions about terminal illness, and other caregiving needs. This paper will systematically examine the current application of multicultural nursing in end-of-life care from five aspects: the impact of culture on the demands of end-of-life care, barriers to implementing multicultural nursing, strategies for cross-cultural communication, training programs to enhance cultural competence, and evidence-based approaches and future research directions. Based on recent international research, it can be seen that cultural differences are serious obstacles to providing end-of-life services, and there is an urgent need to develop nursing models that are both culturally sensitive and flexible. The purpose of this paper is to provide theoretical support and practical suggestions for clinical practice and policy planning in end-of-life care, thereby improving the quality and suitability of services for people of all ethnic groups.